Improving Skills at Calculating Giro Account Balance Using the Snowball Throwing Model in the Subject of Basic Banking at Public Vocational High School 1 of Boyolangu - Sukmasari, Titin; Marsono, Marsono (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2022)
The quality of learning needs to be improved periodically, but not all teachers cannot carry out its improvement. An alternative to be developed to overcome this problem by using active learning strategies is what is called the snowball throwing method. The purpose of this research was to know the improvement of skills at calculating giro account balance by implementing the snowball throwing model to the tenth-grade students of Accounting 1 of Public Vocational High School (PVHS) 1 Boyolangu in the academic year of 2019/2020.This was a classroom action research conducted in four stages in three cycles. The four stages included planning, action, observation, and reflection. For the accurate result of the research, the data collected were statistically analyzed using the mean formula. Based on the result of the analysis and observation during action taking, it can be concluded that the implementation of the snowball throwing model to the 2019/2020 tenth-grade students of Accounting 1 of PVHS 1 Boyolangu helped improve their skills at calculating giro account balance. The conclusion was based on the fact that the average score increased from 67.08 in cycle I to 87.22 in cycle II. In the same way, classical learning completeness increases from 55,56% in cycle I to 100 percent in cycle II